2014
DOI: 10.1111/fwb.12470
|View full text |Cite
|
Sign up to set email alerts
|

Modelling nutrient transport and transformation by pool‐breeding amphibians in forested landscapes using a 21‐year dataset

Abstract: 1. Migrations of animals can transfer energy and nutrients through and among terrestrial and aquatic habitats. Pool-breeding amphibians, such as the wood frog (Lithobates sylvaticus), make annual breeding migrations to ephemeral wetlands in forest habitats in the eastern and midwestern United States and Canada. 2. To model the influence of wood frogs on nutrient transport and transformation through time, we coupled long-term population monitoring data from a wood frog population with estimates of the elementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 54 publications
2
68
0
Order By: Relevance
“…The effects of the loss of amphibian communities on aquatic ecosystem functions have been well-studied (Connelly et al, 2008;Rugenski et al, 2012;Whiles et al, 2013;Rantala et al, 2015), but both amphibians and many aquatic insects have terrestrial adult stages. The movement of organisms from aquatic ecosystems to the terrestrial environment can represent a significant nutrient sink to aquatic ecosystems and an important subsidy to their surrounding terrestrial counterparts (Sabo and Power, 2002;Vanni et al, 2013;Capps et al, 2015b). Variation in %P among populations of Rhinella and Thraulodes can lead to variation in P export to the surrounding terrestrial ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of the loss of amphibian communities on aquatic ecosystem functions have been well-studied (Connelly et al, 2008;Rugenski et al, 2012;Whiles et al, 2013;Rantala et al, 2015), but both amphibians and many aquatic insects have terrestrial adult stages. The movement of organisms from aquatic ecosystems to the terrestrial environment can represent a significant nutrient sink to aquatic ecosystems and an important subsidy to their surrounding terrestrial counterparts (Sabo and Power, 2002;Vanni et al, 2013;Capps et al, 2015b). Variation in %P among populations of Rhinella and Thraulodes can lead to variation in P export to the surrounding terrestrial ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…For example, several studies have shown post-metamorphic survival significantly increases with increased size of post-metamorphic individuals and decreased developmental time–in our study size was greater in individuals raised in treatments with high nutrient quality litter and developmental time was marginally significant. Additionally, export of post-metamorphic anurans can be considered a flux of energy and nutrients into surrounding terrestrial habitat [49,50]. When considering anuran-driven ecosystem functions within lentic and adjacent systems, a decrease in survival will limit the number of individuals present; however, if the individuals are larger due to higher nutrient quality of plant material (invasive or non-invasive) some ecological functions could remain unchanged across wetlands with high nutrient quality plants.…”
Section: Discussionmentioning
confidence: 99%
“…They also embody a significant transfer of energy and nutrients from wetland to upland systems [28][29][30]. These roles are especially pronounced for wood frog metamorphs, which are produced by the thousands in boom years, and because wood frogs, having a relatively short life-span, depend on recruitment for persistence [23,61,62].…”
Section: Metamorph Productivitymentioning
confidence: 99%
“…Metamorph productivity thus constrains the number of dispersal propagules on the landscape. Second, metamorphs are a significant vector for transfer of energy and nutrients from the aquatic into the terrestrial system [28][29][30]. Finally, since eggmasses and larvae are confined to the pool basin and, unlike adults, cannot escape negative habitat conditions by moving to a different location, treatment impacts may manifest sooner or be more severe in these life stages.…”
Section: Introductionmentioning
confidence: 99%